Clinical Outcomes Of Curcumin And Ornidazole Gel As Adjuncts To Nonsur gical Periodontal Therapy (Academia Journal of Medicine, 2026)
Background: Local drug delivery systems are frequently used as adjuncts to scaling and root planing (SRP) to improve clinical outcomes in the management of chronic periodontitis. Curcumin, a naturally derived anti-inflammatory and antimicrobial agent, has emerged as a potential alternative to conventional antimicrobials such as ornidazole. Aim: To comparatively evaluate the clinical efficacy of curcumin gel and ornidazole gel as adjuncts to nonsurgical periodontal therapy in patients with chronic periodontitis. Materials and Methods: This randomized split-mouth clinical study was conducted on twenty systemically healthy individuals of both sexes aged 30–45 years, diagnosed with chronic periodontitis and presenting with bilateral periodontal pockets ≥5 mm. Following full-mouth scaling and root planing, curcumin gel and ornidazole gel were locally delivered into periodontal pockets in symmetric quadrants. Clinical parameters including plaque index (PI), probing pocket depth (PPD), and clinical attachment level (CAL) were recorded at baseline and at 30 days post-treatment. Results: Both treatment groups showed significant improvement in all clinical parameters at the 1-month follow-up. However, sites treated with curcumin gel demonstrated a statistically greater reduction in PPD and PI, along with superior CAL gain, compared to sites treated with ornidazole gel. Conclusion: Within the limitations of the present study, curcumin gel showed more favorable clinical outcomes than ornidazole gel when used as an adjunct to scaling and root planing. Curcumin may therefore be considered an effective and biocompatible adjunct in the nonsurgical treatment of chronic periodontitis.
Keywords: Curcumin; Ornidazole; Local drug delivery; Scaling and root planning